Plautus and the authorial collaboration - Rodrigues da Silva, José Guilherme (Romanitas - Revista de Estudos Grecolatinos, 2023)
An author, while producing a text, can get help from other people in the form of suggestions, or even accept small interpolations in the text which, however, do not change the plot, storyline, structure, theme, or the continuity of the original writing. This kind of help is called authorial collaboration. As any text, theatrical texts are subject to the same small interferences, for example, by actors or producers. We seek in this work discuss the probable occurrence of authorial collaboration in Plautus’ theatrical texts.
Keywords: Authorial collaboration; Theatrical texts; Plautus; Roman theater